Integrating a Human-Centered Design Approach in a Human Trafficking Hackathon - Kathryn Seigfried-Spellar; Chad Laux; Nathan Mentzer (Irish Journal of Academic Practice, 2022)
Human trafficking is a global epidemic that results in grave violations of human rights for approximately 24.9 million people worldwide. The National Academy of Engineering states human-centered design is appropriate for addressing Grand Challenges; thus, the fact that human trafficking intersects with multiple UN agencies and sustainable development goals signifies the need for holistic, interdisciplinary approaches to this global epidemic. Design thinking supports the development of diverse ideas, which are critical for innovation. In this paper, we describe a university-wide event that applied a human-centered design approach to the problem of human trafficking. In this paper, we describe a human to develop potential solutions in mitigating/ending the crime of human trafficking. We organized a university event, inviting experts, faculty, students, staff, and the interested local community to demonstrate that higher education institutions can have an impactful role on human trafficking and potentially effect change. While previous hackathons utilize existing datasets, this was a novel approach in that no data was formally provided to the student teams. The human-centered design approach was successful in facilitating innovation. In addition, the diversity of majors and student team mentors were important in the variety of socio-technical solutions developed by the student teams.